Aromatic profile of Canaiolo nero wines in Santa Catarina highlands, Brazil (Revista de Ciências Agroveterinárias, 2018)
Highlands are a new frontier to produce fine wines in the Southern region of Brazil (27º 12' 24" S, 51º 06' 96" W, 1211 m altitude) and has presented specific oenological characteristics with a good adaptation of some varieties, among them, Canaiolo nero. To characterize the wines of this region, during the 2012 and 2014 harvests the volatile compounds were determined through the MHS-SPME-GC-MS technique. The grapes were harvested, and samples analyzed in triplicate. The positive identification of the volatile compounds was performed by comparing the experimentally obtained mass spectrum and retention index with the reference spectra and retention indices available in the literature. Four consecutive extractions were used for quantitative evaluation to avoid a matrix effect. Odor activity value was calculated from the perception threshold for each evaluated compound. The mean soluble solids content was 21.55o Brix, and total acid content was 81.0 meq L-1; the mean weight of the clusters was 176 g, and the productivity was 2.2 tons per hectare (espalier – 1.5 m × 3.0 m). Thirty-one volatile compounds were identified and quantified in the analyzed samples. The major components were the aromatic alcohol 2-phenylethanol (38.364 µg L-1), and the esters diethyl succinate (6.357 µg L-1) and ethyl acetate (2.005 µg L-1); and the compound of class C6, 1-hexanol (3.2 µg L-1). Odor activity values showed the compounds that contribute the most to the aroma of the analyzed wines, highlighting ethyl isovalerate (OAV 394.38), ethyl hexanoate (OAV 9.22), ethyl cinnamate (OAV 8.62) ethyl isobutanoate (OAV 5.59), β-damascenone (OAV 2.44), hexanoic acid (OAV 4.03), octanoic acid (OAV 3.64) and isoamyl acetate (OAV 3.01). These results showed the aroma characteristics of Santa Catarina wines of the Canaiolo nero variety, especially fruity aromas of apple, green apple, strawberry, plum and banana; and floral aroma of violet and roses.
Keywords: Vitis vinifera; odor activity value; chromatograph; threshold; volatile compounds.; volatile compounds